Exuberance, bubbles and bubble contagion in the portuguese housing market: a perspective from disaggregate bank evaluations - Huget, René (2020)
Bubbles in housing markets can impact the macroeconomy via wealth effects and the banking system via credit backed by overvalued collateral. Housing bubbles also reduce affordability of shelter as a basic need. This paper finds bubbles/exuberance in the Portuguese housing markets using suitable empirical methods. Evidence for bubble contagion from Lisbon and Porto towards surrounding housing markets is provided. Alternative explanations for the findings are discussed. Further, the work sheds light on the link between housing bubbles and the banking system; and provides possible policy suggestions addressing the current bubble behaviour.